2008
DOI: 10.1111/j.1540-8159.2008.01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmic Risk Evaluation during Exercise at High Altitude in Healthy Subjects: Role of Microvolt T‐Wave Alternans

Abstract: In spite of an enhanced sympathetic activity, MTWA testing during exercise at high altitude was negative in all participants. Healthy trained subjects during exercise under hypoxia seem to be at low risk for dangerous arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Increased sympathetic activity reduces the ventricular fibrillation threshold14 and is able to provoke ventricular arrhythmias 15. Exposure to environmental stressors such as cold water6,16 but also high altitude17 per se leads to enhanced sympathetic activity which is further accentuated by exercise 18. The increase in the number of PVCs during cold water exposure, therefore, raises some concerns in regard to the safety of cold water immersion and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Increased sympathetic activity reduces the ventricular fibrillation threshold14 and is able to provoke ventricular arrhythmias 15. Exposure to environmental stressors such as cold water6,16 but also high altitude17 per se leads to enhanced sympathetic activity which is further accentuated by exercise 18. The increase in the number of PVCs during cold water exposure, therefore, raises some concerns in regard to the safety of cold water immersion and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Despite enhanced sympathetic activity, MTWA testing during exercise at HA was negative in all participants. 38 The authors concluded that there is a low risk of dangerous arrhythmias in healthy trained subjects during exercise under hypobaric hypoxia conditions. The possibility, however, of an increased arrhythmic risk in patients with heart diseases favouring arrhythmias, remains an issue yet to be properly addressed in future studies.…”
Section: Arrhythmias and Implantable Devicesmentioning
confidence: 99%
“…Heightened sympathetic activity associated with rapid ascent to elevated altitude and subsequent exercise may increase the frequency and duration of supraventricular and ventricular arrhythmias in healthy volunteers (Alexander 1999;Faulhaber et al 2007;Gibelli et al 2008). Because of this, we examined our healthy subjects until the 3rd week of their stay at elevated altitude, i.e.…”
Section: Discussionmentioning
confidence: 99%